1982
DOI: 10.1042/bj2070641
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between protein thermostability and resistance to proteolysis

Abstract: The loss of activity due to proteolysis of purified L-asparaginase and beta-galactosidase from different sources correlates with the thermal instability of the enzymes. A similar correlation is found when populations of soluble proteins from micro-organisms grown at different temperatures are compared for proteolytic susceptibility and thermal stability. It is proposed that there is a general correlation between the thermostability of proteins and their resistance to proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(67 citation statements)
references
References 18 publications
3
64
0
Order By: Relevance
“…By contrast, I3C NMR relaxation experiments have shown that no correlation exists between thermostability and mobility on the nanosecond time scale (Wuthrich et al, 1980). The increased resistance of thermophilic proteins to proteolysis (Daniel et al, 1982;Fontana, 1988) does not necessarily imply flexibility on a short time scale because global or subglobal unfolding may be required for proteolysis to occur. Such global or subglobal unfolding is probably irrelevant to enzyme catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, I3C NMR relaxation experiments have shown that no correlation exists between thermostability and mobility on the nanosecond time scale (Wuthrich et al, 1980). The increased resistance of thermophilic proteins to proteolysis (Daniel et al, 1982;Fontana, 1988) does not necessarily imply flexibility on a short time scale because global or subglobal unfolding may be required for proteolysis to occur. Such global or subglobal unfolding is probably irrelevant to enzyme catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the engineering of a 340-fold increase in stability at 100°C in a Bacillus stearothermophilus protease by eight site-specific mutations 34 was achieved without compromising catalytic activity, contradicting the dogma that molecular stability and activity are reciprocally related (through global conformational flexibility). Furthermore, there is good evidence for a general correlation between molecular stability to temperature and to other denaturing conditions 35,36 , suggesting common initiators and/or pathways of protein denaturation, whether induced by high temperature, extremes of pH, or the presence of organic solvents or detergents. The practical consequence of this observation is that the selection of a more thermostable enzyme variant (e.g., derived from a thermophilic source) or the engineering of enhanced thermostabil-ity may also result in increased molecular resistance to a range of deleterious conditions.…”
Section: Page |mentioning
confidence: 99%
“…It is required so that enzymes have sufficient flexibility to perform their catalytic functions. An additional requirement for instability can be inferred from the finding that, irrespective of whether or not they are denatured, stable proteins are more resistant to proteolysis [65]. Excessively stable enzymes may therefore hinder the normal cellular turnover of enzymes.…”
Section: Inter-relationship Of Enzyme Stability and Activitymentioning
confidence: 99%